ANALISIS KEWAJIBAN PERPAJAKAN OLEH KAUR KEUANGAN DESA (STUDI KASUS DI KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA) - Nastiti Mintje; Lintje Kalangi; Novi Swandari Budiarso (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
The APBN is a source of village fund income which is transferred through the APBD. The potential for tax revenue on village funds whose value is not small must be a concern and we cannot forget, considering that taxes are the largest source of state revenue. All of these things are closely related to tax compliance. The purpose of this study was to analyze how the implementation of the task of financial management in the administration of taxation on village funds and what obstacles were encountered in the implementation of these tasks and to analyze what factors influenced compliance/non-compliance of the taxation of village funds in the administration of taxation of village funds. This research is a qualitative research with content analysis method as a data analysis technique and the researcher himself as a research instrument. Respondents selected were 6 financial heads in West Tompaso District. Data collection techniques by observation, interviews, and documentation. The results showed that the understanding of financial accounting related to tax obligations on village funds was adequate, but only based on transactions that were often carried out and depended on siskeudes in calculating tax rates. Financial heads are still not compliant with the timeliness of tax payments and tax reporting.